Fibrinolytic, Anti-Inflammatory and Cytotoxic Potentialities of Extracts and Chemical Constituents of Manglicolous Lichen, Graphis ajarekarii Patw. & C. R. Kulk - Tatipamula, Vinay B.; Vedula, Girija Sastry (Natural Products Journal, The, 2020)
Background: Lichens which are betide to mangroves are termed as Manglicolous Lichens (ML). As these ML are habituated under stress conditions, they are screened for unique metabolites and biological activities. Objective: The study aimed to establish the chemical and biological profile of ML, Graphis ajarekarii. Methods: The Ethyl Acetate Extract of G. ajarekarii (EAE) was subjected to chromatographic techniques and the obtained isolates were characterized by spectroscopic analysis. The hydroalcoholic extract of G. ajarekarii (AE), EAE, isolates and Hydroalcoholic Extract of host (HE) were evaluated for fibrinolytic (fibrin clot method), in vitro (protein denaturation method) and in vivo (formalin-induced rat paw oedema assay), anti-inflammatory and cytotoxicity (MTT assay) activities. Results: Chemical investigation of the EAE led to the isolation of two known compounds namely atranorin (1) and ribenone (2), which were confirmed by spectral data. The AE and EAE gradually lysed the fibrin clot with 94.54 and 65.07%, respectively, at 24 h. The AE inhibited protein denaturation of about 88.06%, while the standard (Indomethacin) with 93.62%. Similarly, the in vivo antiinflammatory analysis of AE (200 mg/mL) showed potent reduction of rat paw oedema than the standard, whereas EAE and 1 depicted moderate depletion. In addition, the AE revealed prominence inhibition on MCF-7, DU145 and K-562 with IC50 values of 69.5, 42.5 and 38 μg/mL, respectively, whereas the HE exhibited mild inhibitory profile against fibrin clot, inflammation and cancer. Conclusion: From the results, it can be concluded that the G. ajarekarii has an aptitude to act against coagulation, inflammation and cancer cells.
Keywords: manglicolous lichen